Poverty effects of the Philippines' tariff reduction program: Insights from a computable general equilibrium analysis - Cockburn, John; Corong, Erwin; Cororaton, Caesar B. (Wiley, 2008)
A computable general equilibrium micro‐simulation model is used to assess the economic and poverty impacts of tariff reduction in the Philippines. Tariff reduction induces consumers to substitute cheaper imported agricultural products for domestic goods, thereby resulting in a contraction in agricultural output. In contrast, tariff reduction reduces the domestic cost of production, benefiting the outward‐oriented and import‐dependent industrial sector. The national poverty headcount decreases marginally as lower consumer prices outweigh the nominal income reduction experienced by the majority of households. However, both the poverty gap and severity of poverty worsens, implying that the poorest of the poor become even poorer.